THUMPD3-ASI Is Correlated With Non-Small Cell Lung Cancer And Regulates Self-Renewal Through miR-543 And ONECUT2 - Hu, Jia; Chen, Youfang; Li, Xiaodong; Miao, Huikai; Li, Rongzhen; Chen, Dongni; Wen, Zhesheng (OncoTargets and therapy, 2019)
Background: Of all malignancies, lung cancer is the leading cause of death, and non-small cell lung cancer (NSCLC) accounts for 80-85% of all lung cancers. In this study, the long non-coding RNA (lncRNA) THUMPD3-AS1 was observed to be highly expressed in NSCLC and correlated with TNM stages and relapse, suggesting that THUMPD3-AS1 is involved in the regulation of NSCLC. Methods: The aim of this study was to investigate the regulatory function and mechanism of THUMPD3-AS1 in NSCLC cells by cellular function and molecular biology experiments. Results: Overexpression and knockdown analysis revealed that THUMPD3-AS1 promoted tumor progression by increasing cell proliferation and self-renewal of NSCLC cells. Moreover, THUMPD3-AS1 may act as an endogenous sponge of microRNA-543 (miR543) which can regulate the target gene ONECUT2 in NSCLC cells. Conclusion: Our study indicated that THUMPD3-AS1 regulated NSCLC cell self-renewal by regulating the expression of miR-543 and ONECUT2, and THUMPD3-AS1 can potentially act as a biomarker or therapeutic target in NSCLC. Keywords: non-small cell lung cancer, self-renewal, THUMPD3-AS1, miR-543, ONECUT2